Desenvolvimento de um método analítico rápido e eficiente para a determinação de corticosteroídes plasmáticos por injeção direta em coluna cromatográfica ISRP-C18 por CLAE - Toledo-Pinto, E. A. [UNESP]; Menezes, M. L. [UNESP]; Pereira, O. C.M. [UNESP] (Ecletica Quimica, 2010)
The present work had as aim the development of simple an analytical method, fast efficient and the determination of corticosteroids (cortisone, corticosterone, acetate of hidrocortisone and acetate of dexametasone) in sanguine samples of rats using an isocratic system of liquid chromatography of high efficiency (CLAE) with ultraviolet detention. The method involved direct injection of sanguine sample in a chromatographic column with internal surface of phase reverse (ISRP-C18), using the composed mobile phase for drain plug phosphate pH 4,0: acetonitrile (65:35 v/v). The detention the analytes was obtained using an ultraviolet detector of changeable wave length (Varian Model 2550) adjusted in 240 nm and a 4400 integrator SP Chromaject (Varian Associates, Inc., Sunnyvale, CA, USA). The extraction of the analyte resulted in recovery values between 90% and 108%, and variation coefficient enter 1,1% and 2.5%. The detention and quantification limits of the method were 0,02 and 0,04 μg mL-1, respectively. In conclusion, the analytical method possible the direct injection (on-line) of the sample without previous treatment also presenting some advantages, such as: fast, exactness, precision and specific.
Development of a fast and efficient analytical method for the determination of plasma corticosteroids by direct injection on an ISRP-C18 chromatographic column using HPLC
Keywords: CLAE; Column ISRP- C18; Corticosteroids; Sanguine samples